Faktor yang Berhubungan dengan Ketidakberhasilan Pengobatan Tuberkulosis Usia Produktif di Balai Besar Kesehatan Paru Masyarakat (BBKPM) Surakarta Tahun 2015 - Rahmawati, Novita; , Yuli Kusumawati, SKM., M.Kes (Epid); , Anisa Catur Wijayanti, SKM., M.Epid (2016)
Tuberculosis is still one of the a public health problem in the world despite the control efforts with the DOTS strategy has been implemented in many countries since 1995. In Indonesia by 2015 Tuberculosis treatment success rate is 85% decreased compared to in 2014, amounting to 90.1%. This research aims to know the dominant factor in the unsuccess treatment in sufferers pulmonary Tuberculosis at the productive age in BBKPM Surakarta by 2015. Design research is the case control study. The population in this study sufferers undergoing treatment pulmonary Tuberculosis in BBKPM at the productive age of 15-64 years by as much as 150 sufferers. The selection of sample cases i.e. sufferers who are not successful in the treatment of TB sufferers as much as 29 using the technique of Sampling Exhaustive and sample control i.e. the sufferers recovered within as many as 58 TB treatment sufferers using Cluster Random Sampling. Bivariate analysis using Chi-Square and multivariate analysis using Logistic Regression. The results of the bivariat research shows that there is no relationship between the nutritional status (p=0,471) with thenunsuccess of the treatment of pulmonary Tuberculosis. There is a relationship between the motivation of sufferers (p = 0.000), family support (p = 0.002), and the PMO's role (p = 0.001) with the unsuccess of the treatment of pulmonary Tuberculosis in BBKPM of Surakarta. While the multivariate results showed that motivation is the most dominant factor sufferers against the unsuccessful treatment of Tuberculosis has the highest OR of 33,777 (95%CI= 7,270-156,936).